October fury - Huchthausen, Peter A. (J. Wiley & Sons, 2002)
In the fall of 1962, Huchthausen (Hostile Waters) was a junior navy officer on the USS Blandy, a Forrest Sherman class destroyer; he and his fellow crew members were center stage during the Cuban missile crisis as they confronted Soviet submarines and merchant ships off the coast of Cuba. The submarines were equipped with nuclear-tipped torpedoes and had been given secret orders to use those new and virtually untested weapons if American forces attacked them or if American submarine-hunting destroyers forced them to the surface. That set of circumstances came very close to leading to an exchange of tactical nuclear weapons-an event that likely would have sparked nuclear war between the United States and the Soviet Union. Huchthausen details the story of what happened in those waters in this riveting account, based on his own experience and extensive interviews he conducted with former Soviet submariners and his former shipmates. Through reconstructed dialogue (and plenty of naval technospeak), he reveals that nuclear war was averted primarily by the heroic actions of three of the players in the high seas drama: Comdr. Edward G. Kelley, the Blandy's quixotic but experienced commanding officer; Capt. Nikolai Shumkov, who courageously and conscientiously commanded one of the four Soviet subs in Cuban waters; and Rear Adm. Leonid F. Rybalko, another veteran naval officer who, from his base in Moscow, countermanded dangerous orders from his superiors and paved the way for a peaceful denouement of the tense confrontation at sea. Nicely balanced between operational and analytical material, this account should satisfy action-seeking lay readers and buffs.